Effect of Biochar on Strawberry Growth, Soil Properties and Ecosystem Gas Exchange - Razzaq, Sumyya (2022)
Biochar creates a resistant soil carbon pool that is carbon-negative, provides long-lasting improvements in soil fertility and serves as a net withdrawal of atmospheric carbon dioxide stored in highly stable soil carbon stocks. The enhanced nutrient retention, improved soil fertility and water holding capacity of biochar-amended soil not only reduces the total fertilizer requirements, but also the climate and environmental impact of croplands with generally increased production. I hypothesized that biochar increases plant growth by ameliorating negative soil physicochemical, and enhancing microbial, properties with special relation to nutrient availability and contributes actively to modify ecosystem gas exchange. Moreover, I hypothesized that the rate of biochar application influences the rate of biochar surface oxidation, nature and mineralization of functional groups, when it was added to soil for a long period of time in a controlled environment. The present study focused on determining the potential of a wood-based, high temperature (1100°C) biochar, to increase strawberry plant growth and ecosystem gas exchange in topsoil and its influence on soil quality. The results discussed in this thesis were obtained from a long-term investigation conducted under controlled conditions and is novel because of its duration (18 months), and because of the use of biochar derived from demolition wood. There is currently much interest in utilising biochar as a soil amendment for increased soil health and for carbon sequestration and European and International voluntary standards for biochar safety are under review in the UK post-Brexit. All work on biochar to date, has utilised biochar from virgin wood or agricultural residues. To the best of my knowledge, this is the first study to quantify effects of biochar derived from demolition wood on soil health. The importance of this is twofold; firstly, the stock of virgin wood for biochar production is limited, therefore it is important to be aware of any dangers of ‘diluting’ virgin wood with unapproved feedstock during production, and secondly, it is possible that biochar from such feedstocks might be acceptable for restoration programmes of already contaminated land. Biochar (0, 2.5, 5, 10 and 15% w/w) was mixed with topsoil, added to 14 L pots and maintained in a growth room at 20/16°C (16 hours day/night) and 50 % relative humidity for 18 months. Pots were either planted or left bare and soils in planted and unplanted pots were regularly sampled for microbiological and soil chemical determinations and plant growth measured. Biochar addition did not affect strawberry shoot growth or carbon or nitrogen content, but the 2.5% addition of biochar slightly increased root biomass, whilst the highest concentration (15%), reduced biomass relative to the 2.5% amendment, but not to the control. In the strawberry shoot, K, P, Zn, Cu, and As concentrations increased with biochar addition, while Pb content decreased with increasing rate of biochar compared to the control. Other than these, none of the shoot or root elements analysed exhibited clear biochar-driven trends. Neither leaf conductance nor leaf temperature were affected by biochar amendment. However, biochar amendment generally reduced ecosystem respiration (Re), net ecosystem exchange (NEE), gross ecosystem exchange (GEE) and soil enzyme activities.